Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s10886-008-9586-0
|View full text |Cite
|
Sign up to set email alerts
|

NMR Metabolomics of Thrips (Frankliniella occidentalis) Resistance in Senecio Hybrids

Abstract: Western flower thrips (Frankliniella occidentalis) has become a key insect pest of agricultural and horticultural crops worldwide. Little is known about host plant resistance to thrips. In this study, we investigated thrips resistance in F 2 hybrids of Senecio jacobaea and Senecio aquaticus. We identified thrips-resistant hybrids applying three different bioassays. Subsequently, we compared the metabolomic profiles of these hybrids applying nuclear magnetic resonance spectroscopy (NMR). The new developments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(158 citation statements)
references
References 54 publications
(55 reference statements)
7
144
2
Order By: Relevance
“…There are many examples of negative associations between the fl avonoids present in herbaceous/woody plant species and insects. Leiss et al [48] showed that resistant hybrids contained higher amounts of the fl avonoid kaempferol glucoside. Flavonoids are generally involved in plant resistance to herbivores [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…There are many examples of negative associations between the fl avonoids present in herbaceous/woody plant species and insects. Leiss et al [48] showed that resistant hybrids contained higher amounts of the fl avonoid kaempferol glucoside. Flavonoids are generally involved in plant resistance to herbivores [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…We successfully applied this approach on different host systems including Senecio as a wild plant [2,3], chrysanthemum [4] and gladiolus as ornamentals and tomato [5] and carrot [6] as vegetables. In all host systems the metabolomic profiles of thrips resistant and susceptible plants were significantly different, leading to different metabolites involved in thrips resistance.…”
Section: Eco-metabolomic Approachmentioning
confidence: 99%
“…But for all methods, one should also consider the time needed for extraction and sample preparation, which in the case of GC is far more complicated, as a chemical derivatization step is required, whereas in the case of NMR the extraction can be done with the deuterated NMR solvent. [24][25][26][27][28][29][30][31][32][33] …”
Section: High-throughput Analysismentioning
confidence: 99%
“…These tools can be applied in a broad variety of applications: quality control of medicinal plants (Ephedra spp., [24] Ginkgo biloba [25] ), plant resistance against pests and diseases (Senecio spp., [26] Brassica rapa, [27] Catharanthus roseus, [28] tobacco [29] ), identifi cation of active compounds in medicinal plants (Galphimia glauca [30] ), and chemotaxonomy (Ilex spp., [31] cannabis, [32] Strychnos spp. [33] ).…”
Section: Public Metabolomic Databasementioning
confidence: 99%